Developing Teaching Materials for English Aircraft Engineering Course in Skill-based Learning - Ahmad Rossydi; Benny Kurnianto; Muawal Al Asyari; Adhitya Octavianie; Hendri Louis Latif (Jurnal Ilmu Pendidikan, 2025)
Teaching materials can be defined as all forms of materials that are arranged systematically to enable students to learn by designing them according to the applicable curriculum. The formulation of the problem in this research is how to design teaching materials and how to improve learning outcomes in Engineering and English Communication courses using a skills-based learning model. This research adapts the Research and Development (R&D) model from Thiagarajan with four stages, namely Define, Design, Development and Dessimination or abbreviated as 4D. According to Thiagarajan's 4D model, the 4 stages used include (1) Define, namely defining precisely the expected learning media through analyzing the current situation and learning media needs; (2) Design consists of designing the required features, designing component requirements, selecting English Engineering and Communication learning materials; (3) Development or manufacturing includes creating, preparing English engineering and communication practicum work, testing English engineering and communication practicum materials, feasibility testing for media experts & material experts and product revisions; (4) Dissemination includes spreading the use of products to Aircraft Maintenance Technology cadets, Makassar Aviation Polytechnic and attending national and international conferences. The results of the research show that the design of teaching materials for English Engineering and Communication courses through several stages has received evaluation results which show that the teaching materials developed have succeeded in improving students' English skills, especially in the aspects of reading and speaking and based on the results of evaluations by experts and trials. field, skills-based English Engineering and Communication teaching materials (skill-based Learning) are considered suitable for use in the learning process